Yield load prediction of nailed timber joints using nail diameter and timber specific gravity - Jumaat, Mohd Zamin; Murty, B. (Springer Verlag, 2004)
Prediction of yield load has nowadays been accepted as the basis for the limit state method of the design. Currently, there are many methods to predict the yield load of timber joints. These methods, i.e Foschi, Johansen, Smith and US 5 nail diameter offset, are reviewed in-depth in this paper. In this study, the authors presented a new approach which, hopefully, is simpler than the existing methods. The paper outlines the works carried out to arrive at the formula. About 300 Malaysian timber nailed joints were fabricated and tested to obtain the relationship between yield load and maximum load and to propose a new method to predict the yield load of a nailed joint. There seems to be a direct relationship between the yield load and the maximum load. From this relationship, a new formula, which depends only on nail diameter and specific gravity, was established.